O aluno com deficiência e transtornos de desenvolvimento nas aulas de educação física : aspectos pedagógicos para ação colaborativa do CAD - Alcantara, Laura Yule de Alencar (2024)
This study was developed in order to understand the importance of valuing the functions of the CSD (caregiver of students with disabilities) or TA (therapeutic attendant), in assisting and developing the activities proposed by Physical Education teachers in classes, in order to work on the integral development of students with disabilities or developmental disorders. The main objective was to understand the importance of CSD's participation in helping students with disabilities or developmental disorders to effectively guarantee their integral development through participation in Physical Education classes in the school context. The study methodology is a qualitative approach. The data collection instrument was individual interviews, previously scheduled with each student and their family, a focus group with Physical Education teachers, the pedagogical team and the CSDs involved, from the Municipal School of Basic Education Silva Freire, in Cuiabá-MT, with the intention of identifying and sharing the benefits achieved in Physical Education classes based on the student's participation and experience of pedagogical practices with the help of CSD. The study points out as results of the analysis, the fact that the team involved in the project debated ways to facilitate the routine of the CSD as well as the teachers and families involved, creating a greater learning experience and more enjoyment in classes and in the school routine.